Oil Price and Economic Growth: The Case of Indian Economy - Alkhateeb, Tarek Tawfik Yousef; Sultan, Zafar Ahmad (International Journal of Energy Economics and Policy, 2019)
Oil is an important input used in almost all the economic activities of any country. Hence, rise in its price is likely to adversely affect economic growth of oil importing countries like India. The present paper intends to examine the impact of oil price on economic growth of India. In order to examine the presence of cointegration relationship between economic growth, oil price, capital formation and inflation in the case of India, the study has used Pesaran’s bound test method. The study finds that the variables under study exhibits long run cointegration relationship. VECM results suggest that oil price, capital formation and inflation Granger cause economic growth in the long run. Further, the result shows that the coefficient of oil price is negative and significant implying that oil price in India adversely affects country’s economic growth. The study suggests that the government should refrain from imposing additional taxes in order to avoid rise in oil prices and its subsequent adverse effect on economic growth of the country. Keywords: Oil Price, Economic Growth, Bound Test, India. JEL Classifications: E20, E22, E31 DOI: https://doi.org/10.32479/ijeep.7602